What to offer if consumers do not want what they need? A simultaneous evaluation approach with an application to retirement savings products - Jochen Ruß; Stefan Schelling; Mark B. Schultze (European Actuarial Journal, 2023)
Standard economic models of rational decision making provide information on how people should decide. In practice, human decisions are influenced by numerous behavioral patterns that lead to systematic deviations from rationally optimal behavior. In the context of retirement savings, this can result in substantial pension gaps, and hence in a reduction of the standard of living in the retirement phase. The aim of this work is to introduce a general framework to (simultaneously) assess and evaluate the objectively rational utility and the subjectively perceived attractiveness. We illustrate the approach by means of an application to retirement savings products. Such a combined approach can help to identify or design retirement savings products that create a high (albeit not the maximum possible) objective utility while at the same time being subjectively of high (albeit not maximum possible) attractiveness. We argue that a focus on such products might lead to improved consumer decisions compared to observed decisions that are often driven by subjective attractiveness (resulting in rather low objective utility).
Keywords: D14; G11; G22; G41; J26; J32; 510; Retirement savings; Old-age provision; Utility maximization; Behavioral insurance; Prospect theory; Simultaneous evaluation